(untitled) (Revista Contexto & Educação, 2024)
In this text, we present the analysis of 40 articles on reflective portfolios from a bibliographic mapping of 209 documents on portfolios in teacher education, in reports from online Brazilian journals with Qualis A and B and peer-reviewed journals in Spanish and in English language from the Periodic Portal of the Coordination for the Improvement of Higher Education Personnel – Capes –, covering the period from 1988 to 2020. The objective was to understand the use of reflective portfolios in teacher education. For the methodology, Discursive Textual Analysis, we used a hermeneutic phenomenological approach. Summaries of each category were presented. Next, we give critical arguments present in the literature about the reflexive teacher movement as a structuring concept of teacher education. We argue, in the end, that if reflective portfolios are adopted, the teacher should clarify the theory in which the reflection is situated. In our view, reflective portfolios will be worth the effort if they are linked to pedagogical actions whose thoughts will strengthen struggles for an emancipatory public education. We support the need to include in the pedagogical activities of the formation of thematic teachers referring to the valorization of our profession.